Professional identity of pre-service teachers: actual and designated identity profiles and their relationship to teacher education programs - Meyer, Dennis; Doll, Jörg; Kaiser, Gabriele (Frontiers in Education, 2023)
In this study, we investigated the professional identities of 490 pre-service teachers (PSTs) at the University of Hamburg, Germany. By distributing 100 percentage points, the PSTs assessed the relevance of the roles of subject specialist (SS), didactician (DD), and pedagogue (PD) for themselves currently (actual identity) and for an ideal teacher in different school types (designated identity). A theory-based non-hierarchical cluster analysis distinguished seven profiles: three main role profiles, three dual role profiles, and one balanced profile. The distribution of the PSTs’ actual identities across these seven profiles showed expectedly large interindividual diversity. The most frequent actual identity profiles were those for which the DD and PD roles were particularly relevant (dual role PD/DD profile and balanced profile). The distribution of PSTs across profiles supported the hypothesis that actual identity is related to the type of teacher education program being followed: upper secondary education PSTs were more strongly characterized by profiles that emphasized the SS role (main role SS and dual role SS/DD profiles) than the other PSTs, and special education PSTs were more strongly characterized by profiles that emphasized the PD role (main role PD profile, dual role PD/DD, and PD/SS profiles) than the other PSTs. The designated identities, on the other hand, showed greater consensus among the PSTs. The profiles that best characterized PSTs were the dual role PD/DD profile and the balanced profile. In contrast, the two main role SS and DD profiles and the dual role PD/SS profile were irrelevant as designated identities. A comparison of PSTs’ actual identities with their designated identities showed that a third of the PSTs had the same profile. The diversity of professional identities and the factors in teacher training that influence them should be investigated more closely.